EFFECT OF MULTIMEDIA ACTIVITIES IN BLENDED LEARNING ON LISTENING SKILLS AND SATISFACTION IN A COLLEGE ENGLISH LANGUAGE COURSE - Al-Otaibi, Maryam F.; M. Nouby, Ahmed; Abdul Aziz, Hamdy A.; M. Alagab, Alagab (Journal of Human Capital Development (JHCD), 2012)
This study aimed to investigate the effect of proposed multimedia activities in blended learning on students’ listening skills and satisfaction in a college English language course at the Royal University for Woman (RUW) in Bahrain. The study attempted to assess the effects of the proposed strategy on the students’ listening skills and satisfaction with the multimedia listening activities in the OPL (Orientation Program Lower). Results indicated that experimental group students scored higher level in their listening post-test than those in the control group. Experimental group students were satisfied with the courses designed. KEYWORDS: multimedia activities, interactive multimedia, listening comprehension, blended learning